Active index investing : - Schoenfeld, Steven A. (Wiley, 2004)
Active Index Investing provides a comprehensive overview of (1) the investment theories that are the foundation of index based investing, (2) best practices in benchmark construction, (3) the growing world of index-based investment vehicles, (4) cutting-edge index portfolio management techniq ues and (5) the myriad ways investors can and do capture the benefits of indexing